The research objectives are to analyze impact of human capital investment on income distribution and poverty incidence using the computable general equilibrium (CGE) Model. The model is combined with beta distribution function and Foster-Greer-Thorbecke. The human capital investment is approached by government expenditure for education and health. The simulation result shows that human capital investment is able to increase economic growth and household income. Income distribution especially - Rasidin Karo Karo Sitepu; Bonar M. Sinaga; Rina Oktaviani; Mangara Tambunan (Forum Pasca Sarjana, 2009)
The research objectives are to analyze impact of human capital investment on income distribution and poverty incidence using the computable general equilibrium (CGE) Model.  The model is combined with beta distribution function and Foster-Greer-Thorbecke.  The human capital investment is approached by government expenditure for education and health.  The simulation result shows that human capital investment is able to increase economic growth and household income.  Income distribution especially in rural area becomes more equal which is shown by the beta distribution move to the right side of poverty line.  Poverty incidence, poverty gap and poverty severity also decrease except for non-labor household group in the urban area.  Human capital investment gives more benefit to household in rural area than those in urban area especially for farm-laborer and agriculture entrepreneur household group in the rural area.   Key words: CGE model, Foster-Greer-Thorbecke, beta distribution function, human capital investment, poverty line